MECHANISMS OF THE TERRITORIAL ADMINISTRATIVE DEVELOPMENT IN BULGARIA - Bohdanova, Margarita; Parashkevova, Evelina; Todorov, Yevheni; Tsvetanova, Yeva (Journal of European Economy, 2017)
The concept of regionalization development in the Bulgarian Republic has been substantiated. The evolution of the regional development in the national economy has been revealed. The efficiency in the territorial administrative management has been analyzed. The practice of the territorial management in the market conditions has been demonstrated. Particular attention has been drawn to the analysis of the basic models of strategic planning and regulatory basis. Methods of transition from monocentrism to a moderate polycentrism with its perspective transformation into developed polycentrism have been outlined. Due to the principles of the regional European policy, the financial mechanism of Bulgarian regions, that is oriented toward decrease of the regional differentiations, has been examined. Thus, we can outline the following four strategic aims of the article: to achieve a balanced and contrast regional development; to overcome internal and regional asymmetry in the context of the European cohesion policy; to gain a rational, steady and encompassing increase.